Estimates of the Abundance of Cetaceans in the Central North Atlantic based on the NASS Icelandic and Faroese Shipboard Surveys Conducted in 2015 - Pike, Daniel G.; Gunnlaugsson, Thorvaldur; Mikkelsen, Bjarni; Halldórsson, Sverrir D.; Víkingsson, Gísli (NAMMCO Scientific Publications, 2019)
The North Atlantic Sightings Survey (NASS), the sixth in a series of surveys conducted between 1987 and 2015, was conducted in June/July 2015 and covered a large area of the northern North Atlantic. The Icelandic and Faroese ship survey component of the NASS covered the area between the Faroe Islands and East Greenland from latitude 52° to 72° N. The survey used 3 vessels and an independent double-platform configuration with each platform staffed by a minimum of 2 observers. Here we present both uncorrected abundance estimates derived using Multiple Covariates Distance Sampling, and corrected abundance estimates derived using Mark-Recapture Distance Sampling, for the following species: fin (Balaenoptera physalus), common minke (B. acutorstrata), humpback (Megaptera novaeangliae), blue (B. musculus), sei (B. borealis), sperm (Physeter macrocephalus), long-finned pilot (Globicephala melas) and northern bottlenose (Hyperoodon ampullatus) whales as well as white-beaked (Lagenorhynchus albirostris) and white-sided (L. acutus) dolphins. We then compare these estimates to those from previous NASS and put them into context with estimates from adjoining areas of the North Atlantic.